Postneoadjuvant treatment for triple-negative breast cancer. Issue 6 (19th November 2022) - Trapani, Dario; Ferraro, Emanuela; Giugliano, Federica; Boscolo Bielo, Luca; Curigliano, Giuseppe; Burstein, Harold J.
Abstract : Purpose of review: Triple-negative breast cancer (TNBC) has been conventionally associated with poor prognosis, as a result of limited therapeutic options. In the early setting, prognosis is informed by clinical–pathological factors; for patients receiving neoadjuvant treatments, pathological complete response (pCR) is the strongest factor. In this review, we mapped the landscape of clinical trials in the postneoadjuvant space, and identified three patterns of clinical trial design. Recent findings: For patients at higher risk, effective postneoadjuvant treatments are of paramount importance to address a high clinical need. Postneoadjuvant risk-adapted treatments have demonstrated to improve survival in patients at high of recurrence. Summary: Patients at high risk have indication for adjuvant treatment intensification, informed by baseline clinical, pathological or molecular factors (type 1 approach), on the presence, extent and molecular characteristics of the residual disease at the time of surgery (type 2) or on risk factors assessed in the postsurgical setting (type 3), for example, circulating tumour DNA. Most of the past trials were based on type 2 approaches, for example, with capecitabine and Olaparib. Few trials were based on a type 1 approach, notably pembrolizumab for early TNBC. The clinical validity of type 3 approaches is under investigation in several ongoing trials.